2011
DOI: 10.1002/anie.201007772
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomerism in the Vaptan Class of Vasopressin Receptor Ligands: The Active Conformation Recognized by the Receptor

Abstract: Latent chirality: Atropisomerism in the vaptan class of vasopressin receptor ligands with N‐benzoyl benzo‐fused seven‐membered‐ring nitrogen heterocycles was investigated by freezing the axis by ortho substitution. The aS/aR atropisomers caused by the ArN(CO) axis were separated to reveal that the vasopressin receptor recognizes the cis,aS conformation (see picture; R=CH3, X=CO, Y=H) when it binds to the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…3), 13 and 19 (Schemes 1 and 2). It has previously been reported that compounds of a chemotype similar to the unsubstituted azepine 7 can exist as four possible stereoisomers, 9 arising from a combination of cis/trans isomers of the amidic bond 19 and the presence of atropisomers, resulting from the restricted interconversion of alternative conformations of the azepine ring (Fig. 4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3), 13 and 19 (Schemes 1 and 2). It has previously been reported that compounds of a chemotype similar to the unsubstituted azepine 7 can exist as four possible stereoisomers, 9 arising from a combination of cis/trans isomers of the amidic bond 19 and the presence of atropisomers, resulting from the restricted interconversion of alternative conformations of the azepine ring (Fig. 4).…”
mentioning
confidence: 99%
“…7,8 Natsugari et al have reported that the incorporation of a methyl group at C-6 in the closely related 1,5-benzodiazepine 5 also resulted in the formation of conformational isomers. 9 These atropisomers were separated by chiral HPLC and their absolute configurations determined by X-ray crystallography. The atropisomers of the related analogue 6 exhibited a 9-13 fold difference in affinities towards the human vasopressin V Ia and V 2 receptors.…”
mentioning
confidence: 99%
“…An especially instructive class of atropisomers has been observed recently in the N ‐benzoyl derivatives of the 1,5‐benzodiazepin‐2‐ones class of vasopressin receptor ligands in which the atropisomerism is a result of restricted rotation around an aryl–amide axis . In this class of vasopressin inhibitors there is not only obvious cis / trans isomerization around the appended aryl carbonyl amide bond but also rotational isomerization around the aryl nitrogen axis to form P (aS) and M (aR) atropisomers (see stereo elements depicted in the x‐ray structures in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Tabata et al prepared a number of analogs in which rotation around the aryl–nitrogen bond is frozen to provide isolable and stable atropisomers for biological evaluation . The in vitro affinities of these analogs for human vasopressin hV 1a and hV 2 receptors were quite distinct.…”
Section: Resultsmentioning
confidence: 99%
“…It has been developed as a racemic mixture based on the central chirality of the stereocenter at C5. Later, it was shown that the 5S enantiomer is the eutomer and the 5R isomer the distomer . Interestingly, axial chirality is also present, and thus atropisomers with important pharmaceutical implications may exist .…”
Section: Figurementioning
confidence: 99%